Ответ:
Пошаговое объяснение:
1 . a ) y = 12x - 3 ; 12x - 3 = 0 ; 12x = 3 ; x = 0,25 - нуль функції ;
б) y = x² - 4 ; x² - 4 = 0 ; x² = 4 ; x = ± √4 = ± 2 ; x = ± 2 - нулі ф - ції ;
в) y = √x - 5 ; √x - 5 = 0 ; √x = 5 ; x = 25 ; - нуль функції ;
г) y = x² - 4x ; x² - 4x = 0 ; x( x - 4 ) = 0 ; x = 0 i x = 4 - нулi функції .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1 . a ) y = 12x - 3 ; 12x - 3 = 0 ; 12x = 3 ; x = 0,25 - нуль функції ;
б) y = x² - 4 ; x² - 4 = 0 ; x² = 4 ; x = ± √4 = ± 2 ; x = ± 2 - нулі ф - ції ;
в) y = √x - 5 ; √x - 5 = 0 ; √x = 5 ; x = 25 ; - нуль функції ;
г) y = x² - 4x ; x² - 4x = 0 ; x( x - 4 ) = 0 ; x = 0 i x = 4 - нулi функції .